The Effect of Entrepreneurship Learning and Entrepreneurship Internship on Entrepreneurial Readiness with Motivation as a Mediating Variable among Students of SMKN 2 Batu Malang - Rusno Rusno; Ediyanto Ediyanto; Kristina Sedyastuti (Jurnal Riset Pendidikan Ekonomi, 2026)
The purpose of this study is to analyze the effect of entrepreneurship learning and entrepreneurship internship on entrepreneurial readiness, with motivation as a mediating variable among students of SMKN 2 Batu, Malang. This research employs an explanatory design with a quantitative approach. The population consists of 138 students who have participated in entrepreneurship learning and internship programs, with a total of 103 respondents determined using the Slovin formula. Data were collected through questionnaires and analyzed using WarpPLS version 8.0. The findings reveal that: (1) Entrepreneurship learning has a significant effect on entrepreneurial readiness (P.Value < 0.001, path coefficient = 0.334); (2) Entrepreneurship internship significantly affects entrepreneurial readiness (P.Value < 0.001, path coefficient = 0.292); (3) Motivation has a significant effect on entrepreneurial readiness (P.Value < 0.001, path coefficient = 0.498); (4) Entrepreneurship learning significantly affects entrepreneurial readiness through motivation (P.Value < 0.001, path coefficient = 0.294); and (5) Entrepreneurship internship significantly affects entrepreneurial readiness through motivation (P.Value < 0.001, path coefficient = 0.279). These results indicate that entrepreneurship learning and internships both contribute positively and significantly to students’ entrepreneurial readiness, either directly or indirectly, through enhanced entrepreneurial motivation.